Oportunidades e desafios ao longo do curso de medicina da UFSCar: narrativa crítico-reflexiva - Cruz, Paloma Soares Novello (Universidade Federal de São Carlos, 2023)
Considering the trajectory of a student throughout her graduation, this narrative presents the peculiarities about the medical course of UFSCar, mainly regarding its pedagogical political project, with the objective of developing a critical-reflexive analysis, considering the opportunities offered, but also points that can be improved. Experiences in extracurricular activities that contributed to the student's personal and professional development are also shared.
Opportunities and challenges throughout the medicine course at UFSCar: critical-reflective narrative
Keywords: Metodologia ativa; Pesquisa; Educação médica; Atividades extracurriculares; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM